Community-level HIV intervention in 5 cities: final outcome data from the CDC AIDS Community Demonstration Projects. (1999)
OBJECTIVES: This study evaluated a theory-based community-level intervention to promote progress toward consistent condom and bleach use among selected populations at increased risk for HIV infection in 5 US cities. METHODS: Role-model stories were distributed, along with condoms and bleach, by community members who encouraged behavior change among injection drug users, their female sex partners, sex workers, non-gay-identified men who have sex with men, high-risk youth, and residents in areas with high sexually transmitted disease rates. Over a 3-year period, cross-sectional interviews (n = 15,205) were conducted in 10 intervention and comparison community pairs. Outcomes were measured on a stage-of-change scale. Observed condom carrying and intervention exposure were also measured. RESULTS: At the community level, movement toward consistent condom use with main (P < .05) and nonmain (P < .05) partners, as well as increased condom carrying (P < .0001), was greater in intervention than in comparison communities. At the individual level, respondents recently exposed to the intervention were more likely to carry condoms and to have higher stage-of-change scores for condom and bleach use. CONCLUSIONS: The intervention led to significant communitywide progress toward consistent HIV risk reduction.